PENGARUH IKLIM KOMUNIKASI ORGANISASI TERHADAP MOTIVASI KERJA PADA KARYAWAN LEMBAGA PENYIARAN PUBLIK TELEVISI REPUBLIK INDONESIA RIAU – KEPRI - Nisyia Sasqia Azahra; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
TVRI Riau Station is a local government-owned television station. For Riau TVRI, the motivation given is still limited to the "bonding" of good social relations and the existence of efforts to create creative and productive contributions to instantsi. This study aims to analyze how much influence the organizational communication climate has on the work motivation of TVRI Riau employees.The method used in this research is quantitative research methods with an explanative research design. Data collection techniques by distributing questionnaires directly or using google form. The census sample taken is the entire population, namely all employees of 66 respondents. The data analysis method used is simple linear regression, t test, and testing the coefficient of determination.The results obtained are that the organizational communication climate affects the work motivation of Riau TVRI employees according to hypothesis testing, namely tcount of 5.973> 1.998 and a significance test of 0.000 <0.05 so that Ho is rejected and Ha is accepted. From the simple regression equation Y = 10.832 + 0.374X the value of b = 0.374 means that if the organizational communication climate variable (X) increases by 1%, the effect on work motivation (Y) will increase by 0.374. 35.8% (rounded to 36%). Meanwhile, 64% is a factor that affects the Y variable from other factors not examined by the researcher. What was not studied were employee performance factors, communication satisfaction or job satisfaction factors, employee engagement factors and other factors. Keywords: Organization Climate, Motivation, TVRI Riau-Kepri